2014
DOI: 10.1002/ase.1467
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive load imposed by knobology may adversely affect learners' perception of utility in using ultrasonography to learn physical examination skills, but not anatomy

Abstract: Ultrasonography is increasingly used for teaching anatomy and physical examination skills but its effect on cognitive load is unknown. This study aimed to determine ultrasound's perceived utility for learning, and to investigate the effect of cognitive load on its perceived utility. Consenting first-year medical students (n = 137) completed ultrasound training that includes a didactic component and four ultrasound-guided anatomy and physical examination teaching sessions. Learners then completed a survey on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 57 publications
2
60
0
1
Order By: Relevance
“…Two papers surveyed ultrasound experts using a 'Delphi' methodology to establish ultrasound learning milestones [21] and an assessment tool [22]. Description of subcategory [92][93][94][95][96][97][98] Training medical students in POCUS for 1 year appears to provide them with a significant advantage in the postgraduate arena [92]. Retention of knowledge can be problematic (one paper reported a 17% decrease in knowledge learned after 1 year).…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 2 more Smart Citations
“…Two papers surveyed ultrasound experts using a 'Delphi' methodology to establish ultrasound learning milestones [21] and an assessment tool [22]. Description of subcategory [92][93][94][95][96][97][98] Training medical students in POCUS for 1 year appears to provide them with a significant advantage in the postgraduate arena [92]. Retention of knowledge can be problematic (one paper reported a 17% decrease in knowledge learned after 1 year).…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…The learning curve to enable novices to detect major cardiac abnormalities with acceptable diagnostic value when compared with experienced echocardiographer findings is short [95]. Ultrasound 'knobology' has been shown to be responsible for a large portion of the cognitive load for novice ultrasound learners [96,97]. Gradl-Dietsch et al [98] found no effect of gender on either objective performance during assessment or subjective preference when learning ultrasound.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial stages of these courses instructed students on basic anatomy and ultrasound image interpretation whereas the course would then shift to the use of ultrasound in a clinical context in subsequent years (Hoppmann et al, 2011;Rempell et al, 2016;Wilson et al, 2017). They concluded that because of this, junior students did not receive as great a benefit in terms of their anatomy education (Jamniczky et al, 2015). Some courses offered 2 hr of practical laboratory time per week over 20 weeks (Syperda et al, 2008), whilst others offered 3.5 hr of laboratory time over the entire anatomy course within an academic year (Dreher et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some used multiple cadaveric preparations and manikins to perform common bedside procedures (Benninger, 2015). The staff employed were either trained faculty members or experienced clinicians (Chew, 2002;Butter et al, 2007;Bahner and Royall, 2013;Hoyer et al, 2015;Jamniczky et al, 2015). For example, for a 12-week course composed of lectures and demonstrations, the study investigators 30 hr of work each for two tutors (Wright and Bell, 2008).…”
Section: Resources and Staffing Requiredmentioning
confidence: 99%